Sovereign Bond Yield Differentials across Europe: A Structural Entropy Perspective - Warin, Thierry; Stojkov, Aleksandar (Entropy (Basel, Switzerland), 2023)
This study uses structural entropy as a valuable method for studying complex networks in a macro-finance context, such as the European government bond market. We make two contributions to the empirical literature on sovereign bond markets and entropy in complex networks. Firstly, our article contributes to the empirical literature on the disciplinary function of credit markets from an entropy perspective. In particular, we study bond yield differentials at an average daily frequency among EU countries’ 10-year Eurobonds issued between 1 January 1997, and 4 October 2022. Secondly, the article brings a methodological novelty by incorporating an entropy perspective to the study of government bond yield differentials and European capital market integration. Entropy-based methods hold strong potential to bring new sources of dynamism and valuable contributions to the areas of macroeconomics and finance.